HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN PERAWAT DENGAN SIKAP MENDUKUNG PENERAPAN PROGRAM KESELAMATAN PASIEN DI RSUD BANJARBARU - Wulandari, Nanda; Setyaningrum, Ratna; Musafaah, Musafaah (Universitas Lambung Mangkurat, 2014)
Background: The mortality rate of patients in hospitals need attention related to nursing care which refers to the concept of patient safety.Objective: To investigate the relations between knowledge and attitude characteristics of nurses with supporting the implementation of patient safety programs in Banjarbaru Hospital. Methods: observational study with cross sectional approach. Using a sample of 24 nurses, from a population of 124 nurses. Results: Found a relation between the level of knowledge with an attitude to support the implementation of the program p = 0.000. There is a relation between the age of respondents with an attitude to support the implementation of the program p = 0.031. There is a relation between the period of employment of the respondents with an attitude to support the implementation of the program p = 0.000. There is a relation between training with an attitude to support the implementation of the program p = 0.000.Conclusion: Knowledge and nurse characteristics (age, years of service, and training) have a significant relation with the application of a good attitude about the program supports patient safety.Â Keywords: knowledge, characteristics, attitude, patient safety, Banjarbaru hospital